Cerebral vein thrombosis complicating influenza A in a toddler - Al-Shami, Rana; Al-Ahmed, Amena; Saeed, Amira; Kini, Vishwanatha; Mohame, Khalid (Indian Journal of Child Health, 2018)
We describe a child who presented with a respiratory illness in the influenza pandemic season and was found to be positive for the influenza A, he developed neurological manifestations of cranial nerve palsies and was found to have radiological evidence of cerebral sinus thrombosis. He received treatment with oseltamivir and supportive therapy and was discharged home free of long-term neurological sequelae. This is a rare complication which might have associated with this infection and has not been reported in children before as far as we are aware. Children who develop focal neurological signs during the course of flu epidemic should be evaluated for the possibility of cerebral sinus thrombosis.